Why Acting Environmentally-Friendly Feels Good: Exploring the Role of Self-Image - Venhoeven, Leonie A.; Bolderdijk, Jan Willem; Steg, Linda (Frontiers in Psychology, 2016)
Recent research suggests that engagement in environmentally-friendly behavior can feel good. Current explanations for such a link do not focus on the nature of environmentally-friendly behavior itself, but rather propose well-being is more or less a side-benefit; behaviors that benefit environmental quality (e.g. spending one’s money on people rather than products) also tend to make us feel good. We propose that the moral nature of environmentally-friendly behavior itself may elicit positive emotions as well, because engaging in this behavior can signal one is an environmentally-friendly and thus a good person. Our results show that engagement in environmentally-friendly behavior can indeed affect how people see themselves: participants saw themselves as being more environmentally-friendly when they engaged in more environmentally-friendly behavior (Study 1). Furthermore, environmentally-friendly behavior resulted in a more positive self-image, more strongly when it was voluntarily engaged in, compared to when it was driven by situational constraints (Study 2). In turn, the more environmentally-friendly (Study 1) and positive (Study 2) people saw themselves, the better they felt about acting environmentally-friendly. Together, these results suggest that the specific self-signal that ensues from engaging in environmentally-friendly behavior can explain why environmentally-friendly actions may elicit a good feeling.